Fashion and Desire: The Society of Spectacle in Post Reality - Manurung, Elvy; Alvin, Immanuel (Technium Social Sciences Journal, 2021)
Fashion was a contemporary phenomenon that increasingly developed to meet the needs of users in its digital industry era. The rapid development of fashion has made the industry compete to present the latest fashions faster and faster. The support and advances of the Internet in communication technology have helped to accelerate the spread of power through virtual networks. Digital media have brought people into a new experience, namely "post-reality", that had never existed. This study focuses on fashion consumption in the form of clothes with a fast production scale or fast-fashion along with low costs, as well as sneakers that were consumed by young people. One hundred and twenty-nine students at five universities in West Java Indonesia have interviewed. Using a qualitative method which was supported by the summary of the distribution of questionnaires, conducted throughout 2019 and early 2020, the results of this study were then analyzed using Guy Debord’s theory of spectacle society. The study has found that the consumption of fast fashion and sneakers by students had an impact on their spending patterns, self-identity, self-confidence, and the role of the user as a commodity spectacle in today’s fashion industry.